Elucidating the corrosion-related degradation mechanisms of a Ti-6Al-4V dental implant. Issue 3 (March 2020) - Chen, Xin; Shah, Kumar; Dong, Shiqi; Peterson, Lars; Callagon La Plante, Erika; Sant, Gaurav
Graphical abstract: Abstract: Objective: The Ti-6Al-4V ( TAV ) alloy is commercially used as a dental implant material. This work seeks to elucidates the origins of degradation of Ti-6Al-4V (TAV) implant alloys that result in peri-implant bone loss.  Methods: In this work, a combination of microstructure, surface, and solution analyses was utilized to study the corrosion mechanism of the TAV alloy in oral environments. The corrosion of TAV alloys in the F - -enriched environment of a crevice was evaluated through nanoscale surface analysis. And, the findings were further rationalized via electrochemical means.   Results: Our results suggest the bone loss was caused by crevice corrosion and the consequential release of by-products, and the crevice corrosion was potentially induced by the buildup of corrosive species such as fluorides, which are common additives in dental products. In turn, the corrosion properties of the TAV alloy were evaluated in fluoride enriched environments. Nanoscale analysis of corroded surfaces, carried out using vertical scanning interferometry (VSI) showed that the corrosion susceptibility of the constituent phases dictates the corrosion product species. In specific, the aluminum-rich α phase preferentially dissolves under potential-free conditions and promotes the formation of insoluble Al-Ti oxides. Notably, under conditions of applied potential, oxidative dissolution of the vanadium-rich β phase is favored, and the vanadium release is promoted.   Significance: These findings elucidate the origins of degradation of TAV-implants that result in the release of corrosion by-products into the local biological environment. More important, they offer guidelines for materials design and improvement to prevent this nature of degradation of dental implants.